Employment and social trends by region. Issue 1 (January 2017) - Kühn, Stefan; Milasi, Santo; Horne, Richard; Yoon, Sheena
Abstract: This chapter will assess both across and within regions (i) recent economic and labour market developments; and (ii) short‐term employment and social prospects.